INTERACTION IN THE EVALUATION ACTIVITY IN THE EDUCATIONAL PROCESS OF MODERN UNIVERSITY - Дибкова, Л. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The interaction of all participants in the process of the results evaluation of the training activities of the university students in this article are discussed. These problems are caused by global development and national science, economics and educational practice. The main components are analyzed, designed to improve prospects